MODELING OF THE BEHAVIOUR REOLOGICHESKIH TEL UNDER DIFFERENT LAW NAGRUZHENIYA - V. V. Bendyukov; O. G. Osyaev (Научный вестник МГТУ ГА, 2017)
The Offered model of the behaviour reologicheskogo bodies (the viscous-elasticity of the materia), designs or systems) under controlling influence of the load, acting on given law for some time.